2015
DOI: 10.1186/s13059-015-0849-0
|View full text |Cite
|
Sign up to set email alerts
|

Circlator: automated circularization of genome assemblies using long sequencing reads

Abstract: The assembly of DNA sequence data is undergoing a renaissance thanks to emerging technologies capable of producing reads tens of kilobases long. Assembling complete bacterial and small eukaryotic genomes is now possible, but the final step of circularizing sequences remains unsolved. Here we present Circlator, the first tool to automate assembly circularization and produce accurate linear representations of circular sequences. Using Pacific Biosciences and Oxford Nanopore data, Circlator correctly circularized… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
658
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 903 publications
(659 citation statements)
references
References 26 publications
1
658
0
Order By: Relevance
“…Expected genome size was set to 4,800,000 bp [as indicated by an HGAP 3 trial run (data not shown)]. This approach resulted in two contigs (with mean QV score at 48.8 and 47.7, respectively) that were subsequently circularized by Circlator 0.16.0 (Hunt et al, 2015) using corrected sub-reads generated by HGAP 2 (with 6,000 minimum seed read length). The ‘RS_Resequencing.1’ protocol on SMRT ® Analysis was then used to align raw reads to the circularized genome for an improved consensus.…”
Section: Methodsmentioning
confidence: 99%
“…Expected genome size was set to 4,800,000 bp [as indicated by an HGAP 3 trial run (data not shown)]. This approach resulted in two contigs (with mean QV score at 48.8 and 47.7, respectively) that were subsequently circularized by Circlator 0.16.0 (Hunt et al, 2015) using corrected sub-reads generated by HGAP 2 (with 6,000 minimum seed read length). The ‘RS_Resequencing.1’ protocol on SMRT ® Analysis was then used to align raw reads to the circularized genome for an improved consensus.…”
Section: Methodsmentioning
confidence: 99%
“…The resultant contigs were checked for further joins and circularity using Circlator version 1.5 (10). Contigs were polished using Quiver, part of the SMRT Analysis suite version 2.3 (Pacific Biosciences) (11), and the sequence order was verified using the restriction enzyme AflII for whole-genome mapping (OpGen, Gaithersburg, MD, USA).…”
Section: Genome Announcementmentioning
confidence: 99%
“…The current NCTC manual assembly pipeline uses the HGAP assembler (Chin et al 2013) to produce a list of contigs, and Circlator (Hunt et al 2015) to circularize contigs. The assembly graphs produced by HINGE with no parameter tuning for each of these data sets are available online (http://web.stanford.edu/ gkamath/NCTC/report.html) and in Supplemental Table S4, along with the contig statistics of the NCTC pipeline results and the assembly graph produced by Miniasm (Li 2016).…”
Section: Evaluation On the Nctc Databasementioning
confidence: 99%